Use of Social Media Platforms for Purchasing Fashion Items: A Comparison of US and Chinese Consumers - Shen, Li (Journal of Comparative International Management, 2020)
This paper develops a conceptual connection between the Revised Technology Acceptance Model and Hofstede’s Cultural Dimensions in explicating the adoption by customers of a social media platform in the fashion industry in the context of the US and China. This study shows that the trustworthiness of Facebook is positively related to US customers’ intention to purchase fashion items and the trustworthiness of WeChat is positively related to Chinese customers’ intention to purchase fashion items. Also, US customers’ perceived usefulness is not positively related to the intention of using Facebook to buy fashion items. However, their Chinese counterparts had the opposite result. The findings enhance our understanding of the factors that influence customers’ adoption of social media platforms for purchasing fashion items and provides suggestions for marketing managers as to how they can utilize social media platforms to market fashion items. The paper concludes with a discussion of possible future research in this field.